The model of strategic confrontation between the USA and Russia in the 21st century - E. V. Balatsky (Мир новой экономики, 2025)
The article examines the military-strategic confrontation between the USA and Russia, with a growing tendency toward conflict escalation in Ukraine. It is demonstrated that the observed paradox — the West’s diminishing fear of a “thermonuclear Armageddon” — is driven by the duality of Russia’s position after 1991. On the one hand, Russian elites fell under Western influence, yet on the other, they retained the potential to “rise” and restore the country’s political sovereignty, leveraging its military-strategic capabilities. As a result, another unique phenomenon emerged: the ambiguity of Russia’s “red lines” in foreign policy, as they were either left undefined or continuously shifted. This led to the West becoming accustomed to Russia’s excessive caution and failing to “hear” its new signals. The situation is further reinforced and exacerbated by the United States’ lack of foreign policy flexibility due to its adherence to a mental model of global dominance, which comprises four key elements: the presumption of America’s divine exceptionalism, the doctrine of irreconcilability, the strategy of totality, and the refusal-to-accept-unacceptable-costs syndrome. The effect of power indivisibility, as described by S. Lukes, compounds this model and heightens the insensitivity of the American establishment to the escalation of tensions in Ukraine. The study highlights that the U.S. administration employs two intellectual “legacies” of John Foster Dulles in its strategy: the doctrine of “brinkmanship” and the doctrine of “bearable cost.” Since Russia has not inflicted any tangible damage on the United States, there is no incentive for the latter to abandon Dulles’ legacy or to de-escalate the confrontation. The author argues that to change the situation, it is necessary to ensure unacceptable costs for the U.S. in this confrontation. Specific measures to increase the “cost” of American hegemony are discussed, which could shift the focus from unilateral pressure on Russia toward a more favorable environment for constructive negotiations.